Persepsi Wisatawan Terhadap Objek Wisata Pemandian Air Panas Angseri Kabupaten Tabanan - I Gusti Ayu Adek Febriana Asialiantin Putri; Lulup Endah Tripalupi (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to determine the perception of tourists. It is a descriptive study, which aims to describe the tourist attraction of the Angseri Hot Springs. This type of research is descriptive quantitative. The population in this study were 2,400 tourists visiting Angseri Hot Springs. A sample of 342 respondents was taken using simple random sampling technique. Data were collected using documentation, questionnaires and interviews. Data analysis techniques using descriptive analysis. The results showed that: tourist perceptions of the tourist object of Angseri Hot Springs in terms of (1) attractions, (2) amenities (3) accessibility is in the category of strongly agree with a score of 5863, in terms of the dimensions of the availability of facilities in the very category. agree with a score of 10154, in terms of the accessibility dimension, the category strongly agrees with a score of 7351. This means that the Angseri Hot Spring tourist attraction has a unique and beautiful nature, and there are supporting facilities available to provide easy access to tourist objects to the Angseri Hot Spring.